Magnus Chase and the hammer of Thor - Riordan, Rick (London : Penguin random house Uk, 2016)
In Magnus Chase and the Hammer of Thor, Magnus Chase, a young hero living in the world of Norse gods, faces a new danger when Thor s powerful hammer, Mjölnir, is stolen. To prevent chaos among the gods and humans, Magnus and his friends set out on a risky quest to recover it. Along the way, they confront dangerous giants, tricky gods, and unexpected challenges. The story is full of humor, action, and adventure, while also exploring themes of friendship, identity, courage, and accepting differences.